Vocabulary Mastery and Its Influence on Speaking Skills - Salim, Agus (Lembaga Penelitian dan Pendidikan Mandala, 2025)
his study aims to determine the level of students' vocabulary mastery, to identify their speaking skills, and to find out how significant the influence of vocabulary mastery is on their Indonesian speaking ability. The sampling technique used was random sampling. The research instrument utilized was a questionnaire. Data collection techniques included questionnaires, observation, and documentation. The data analysis techniques used were descriptive and inferential analysis, calculated using simple regression formulas and product-moment correlation. The results of the study show the following: First, the vocabulary mastery variable (X) had a minimum score of 43, a maximum score of 123, and an average score of 83.93, with a standard deviation of 23.081. Second, the Indonesian speaking skill variable (Y) had a minimum score of 7, a maximum score of 21, and an average score of 14.70, with a standard deviation of 4.103. The regression coefficient is positive, indicating that the direction of the influence of variable (X) on variable (Y) is positive and that the relationship between the two variables is very strong.